Some community school practices of the Philippines and their implications for Thailand - Puekham, Prateep 1934- ([Quezon City s.n.], 1962)
This study determines community school practices of the Philippines and the basic concepts, techniques, and procedures connected with the movement. The implications of these concepts and practices for the schools of Thailand were also determined.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Community and school